Advances and challenges on the path toward the SDGs: subnational inequalities in Mexico, 1990–2017 - Rafael Lozano; Marcela Agudelo-Botero; María Cecilia González-Robledo; Claudio Alberto Dávila-Cervantes; Gabriel Martinez; Nancy Fullman; Juan Pablo Gutierrez; Sebastian Garcia-Saiso; Carolina Zepeda-Tena; Christian Razo; Bernardo Hernández-Prado; Simón Barquera (BMJ Global Health)
Background The sustainable development goals (SDGs) have generated momentum for global health, aligning efforts from governments and international organisations toward a set of goals that are expected to reflect improvements in life conditions across the globe. Mexico has huge social inequalities that can affect access to quality care and health outcomes. The objective of this study is to analyse inequalities among Mexico’s 32 states on the health-related SDG indicators (HRSDGIs) from 1990 to 2017.Methods These analyses rely on the estimation of HRSDGIs as part of the Global Burden of Disease study 2017. We estimated the concentration index for 40+3 HRSDGI stratified by Socio-demographic Index and marginalisation index, and then for indicators where inequalities were identified, we ran decomposition analyses using structural variables such as gross domestic product per capita, poverty and health expenditure.Findings Mexico has made progress on most HRSDGIs, but current trends in improvement do not appear to fast enough to meet 2030 targets. Out of 43 HRSDGIs, we identified evidence of inequality between Mexico’s states for 30 indicators; of those, 23 HRSDGIs were unequal distributed affecting states with lower development and seven affecting states with higher development. The decomposition analysis indicates that social determinants of health are major drivers of HRSDGI inequalities in Mexico.Interpretation Modifying current trends for HRSDGIs will require subnational-level and national-level policy action, of which should be informed by the latest available data and monitoring on the health-related SDGs. The SDGs’ overarching objective of leaving no-one behind should be prioritised not only for individuals but also for communities and other subnational levels.